2021
DOI: 10.3390/ijms22094429
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin Misfolding, A Fatal Structural Pathogenesis Mechanism

Abstract: Transthyretin (TTR) is an essential transporter of a thyroid hormone and a holo-retinol binding protein, found abundantly in human plasma and cerebrospinal fluid. In addition, this protein is infamous for its amyloidogenic propensity, causing various amyloidoses in humans, such as senile systemic amyloidosis, familial amyloid polyneuropathy, and familial amyloid cardiomyopathy. It has been known for over two decades that decreased stability of the native tetrameric conformation of TTR is the main cause of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 100 publications
0
15
0
Order By: Relevance
“…Annular oligomers are composed of double stacks of octamers that tend to convert into spheroidal oligomers consisting of 8–18 monomers [ 34 ]. Aggregates of TTR mutant oligomers exhibit higher molecular weight than wild-type aggregates [ 4 ].…”
Section: Amyloid Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…Annular oligomers are composed of double stacks of octamers that tend to convert into spheroidal oligomers consisting of 8–18 monomers [ 34 ]. Aggregates of TTR mutant oligomers exhibit higher molecular weight than wild-type aggregates [ 4 ].…”
Section: Amyloid Formationmentioning
confidence: 99%
“…Seeding relies on the addition of preformed compounds, while nucleation implies the birth of new ones. Many oligomers have been identified in the early stages of fibrillation, serving as a precursor of amyloid nucleation [ 34 ]. Electron microscopic studies have shown amorphous electron-dense materials around microvessels and the subperineural space in addition to speckles or fine fibrillar-structures within the periphery, which may be the core of the amyloid fibrils [ 2 ].…”
Section: Amyloid Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite it is widely accepted that tetramer destabilization is a rate-limiting step for the development of amyloid fibrils [9][10][11][12], TTR proteolysis has been increasingly recognized as another mechanism driving TTR amyloid formation. Several studies reported the existence of different TTR amyloid deposits in a range of tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, proteolysis-induced fragmentation of TTR has been proposed as a mechanism facilitating the development of ATTR amyloidosis [ 36 ]. Amyloid deposits are classified into type A, which consists of a mixture of cleaved TTR and full-length TTR, and type B, which consists only of full-length TTR.…”
Section: Molecular Mechanisms Of Amyloidosismentioning
confidence: 99%